Effect of Irrigation Intervals and Mulching Material on the Growth and Yield of Maize (Bangladesh Agronomy Journal, 2025)
An experiment was conducted at Habiganj Agricultural University's research field to study the effects of irrigation and mulching on the yield of maize cultivation in the Sylhet region of Bangladesh. The study analyzed the effects of different irrigation intervals, i.e., irrigation at 15, 30, and 60 days after sowing (DAS); at 15, 30, and 85 DAS; and at 15, 30, 60, and 85 DAS; along with polythene and jute sack as mulching materials on maize performance. The experiment was laid out in a pot experiment with a randomized complete block design with three replications. Results showed that irrigation at 15, 30 and 85 DAS gave the highest cob length (cm), cob weight plant−1 (g), number of grain cob−1, 100-grain weight (g), and grain yield (t ha−1) while jute sack performed better than mulching with polythene. The interaction effect of irrigation intervals and mulching treatments showed a significant difference in all yield contributing parameters except the number of cob plant−1. The highest cob length (16.57 cm), cob weight plant−1 (143.33 g), number of grain cob−1 (316.65), 100-grain weight (34.33 g), grain weight cob−1 (118.9 g) and grain yield (8.77 t ha−1) were obtained from the interaction of at 15, 30 and 85 DAS intervals with jute sack mulching whereas the lowest from the no irrigation (control) with jute sack mulching.Bangladesh Agron. J. 2024, 27(2): 90-95